Skeletal Stability after Large Mandibular Advancement (> 10 mm) with Bilateral Sagittal Split Osteotomy and Skeletal Elastic Intermaxillary Fixation - Kristoffer Schwartz; Maria Rodrigo-Domingo; Thomas Jensen (Stilus Optimus, 2016)
Objectives: The aim of the present study was to assess the skeletal stability after large mandibular advancement (> 10 mm) with bilateral sagittal split osteotomy and skeletal elastic intermaxillary fixation and to correlate the skeletal stability with the vertical facial type. Material and Methods: A total of 33 consecutive patients underwent bimaxillary surgery to correct skeletal Class II malocclusion with a mandibular advancement (> 10 mm) measured at B-point and postoperative skeletal elastic intermaxillary fixation for 16 weeks. Skeletal stability was evaluated using lateral cephalometric radiographs obtained preoperative (T1), 8 weeks postoperatively (T2), and 18 month postoperatively (T3). B-point and pogonion (Pog) was used to measure the skeletal relapse and the mandibular plane angle (MP-angle) was used to determine the vertical facial type. Results: The mean advancement from T1 to T2 were 11.6 mm and 13.5 mm at B-point and Pog, respectively. The mean skeletal relapse from T2 to T3 was -1.3 mm at B-point and -1.6 mm at Pog. The nineteen patients characterized as long facial types, showed the highest amount of skeletal relapse (-1.5 mm at B-point and -1.9 mm at Pog). Conclusions: The present study showed a limited amount of skeletal relapse in large mandibular advancement (> 10 mm) with bilateral sagittal split osteotomy and skeletal elastic intermaxillary fixation. Bilateral sagittal split osteotomy in combination with skeletal intermaxillary fixation can therefore be an alternative to distraction osteogenesis in large mandibular advancements.